Performance evaluation of AODV ,OLSR, and GRP for transmitting video conferencing over MANETs - Ahmed, Diaa Eldin Mustafa; Ebrahim, Hala A.; Khalifa, Othman Omran (International Journal of Computer Science and Information Security (IJCSIS), 2020)
Transmitting video over Mobile Ad-hoc networks (MANETs) is a challenging task because it is severely affected by the various properties of the MANETs such as mobility, dynamic change in topology, lack of fixed infrastructure, resource constraints and limited bandwidth. Most of the existing MANETs routing protocols are not cope with QoS metrics (E2E-delay, jitter, Packet Delivery Ratio (PDR%)) required to efficiently transmitted video contents. This paper investigates the efficient MANETs routing protocols that can provide a high QoS for video conferencing over MANETs through simulation experiments that vary in network sizes and density of mobile nodes. The simulation carried out through OPNET 14.5 modular. The routing protocols under the investigation are Ad hoc on Demand Distance Vector (AODV) as the reactive routing protocol, Optimized Link State Routing (OLSR) as proactive, and Geographic Routing Protocol (GRP) as position-based. The goal of our simulation is to evaluate the impact of the mobility and scalability on the performance of the above routing protocols for video conferencing over MANET in order to identify which MANET routing protocols grantee the desirable QoS metrics. From our simulation study we found that OLSR outperforms AODV and GRP when MANETs scalable and becomes dense